2011
DOI: 10.1038/ncomms1433
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation regulates oviposition in the pathogenic blood fluke Schistosoma mansoni

Abstract: Similar to other metazoan pathogens, Schistosoma mansoni undergoes transcriptional and developmental regulation during its complex lifecycle and host interactions. DNA methylation as a mechanism to control these processes has, to date, been discounted in this parasite. Here we show the first evidence for cytosine methylation in the S. mansoni genome. Transcriptional coregulation of novel DNA methyltransferase (SmDnmt2) and methyl-CpG-binding domain proteins mirrors the detection of cytosine methylation abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
141
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 57 publications
16
141
2
1
Order By: Relevance
“…1B). Finally, we also used our data for a detailed analysis of the Schistosoma forkhead gene that had previously been reported to be methylated in a Dnmt2-dependent manner (23). Our results failed to reveal any evidence for DNA methylation at the previously analyzed region (Fig.…”
Section: Resultscontrasting
confidence: 44%
“…1B). Finally, we also used our data for a detailed analysis of the Schistosoma forkhead gene that had previously been reported to be methylated in a Dnmt2-dependent manner (23). Our results failed to reveal any evidence for DNA methylation at the previously analyzed region (Fig.…”
Section: Resultscontrasting
confidence: 44%
“…The E. granulosus genome had 48 DLC members (compared to 35 in Schistosoma japonicum and 29 in Schistosoma mansoni), whereas 4-7 were found in the 4 nematodes. We identified 49 cadherins in the E. granulosus genome, similar to the numbers found in schistosomes (51-65) but more than in nematodes (12)(13)(14)(15)(16)(17)(18) (Supplementary Table 22b). Cadherins belong to a class of type 1 transmembrane proteins that have important roles in cell recognition and adhesion.…”
Section: Domain Families Gained In E Granulosusmentioning
confidence: 48%
“…5). Cytosine methylation in the schistosome genome regulates oviposition 12 , but the higher CpG content in worms might hint that such methylation occurs much less frequently in these organisms than in mammals. We found only one DNA (cytosine-5)-methyltransferase gene (gene symbol, DNMT3B; gene ID: EG_07014; KO identifier, K00558) and one methyl-CpG-binding domain gene (MBD; EG_02905; K11590) in the E. granulosus genome (Supplementary Table 13), whereas ten DNMT genes are present in humans.…”
Section: Genome Sequencing and Annotationmentioning
confidence: 99%
“…This process revealed that low levels (∼2.5% of CpGs, based upon a genome-wide average) of modification are present, although we cannot strictly distinguish based upon our analysis between cytosine methylation and other modifications, such as hydroxymethylation. Notably, DNA methylation was not detected in S. mediterranea (37) and there are conflicting reports for S. mansoni (38,39).…”
Section: Resultsmentioning
confidence: 99%